A picture book of Florence Nightingale - Adler, David A. (New York : Holiday House, 1992)
Traces the life of the nineteenth-century English woman who followed her calling to work in hospitals and improve the conditions under which the sick were treated.
Keywords: Nightingale, Florence, 1820-1910 -- Pictorial works -- Juvenile literature; Nurses - England -- Biography -- Pictorial works -- Nurses